Analisis Putusan Hakim Dalam Pembatalan Akta Risalah Lelang: Analysis of the Judge's Ruling in the Cancellation of the Auction Minute Deed - Muhammad Zul Efendi Manurung; Zaenal Arifin; Soegianto, Soegianto (Universitas Semarang, 2025)
This study examines the judicial reasoning underlying the cancellation of Auction Minute Deed Number 1352 year 2010 and analyzes the resulting legal consequences along with the legal protection afforded to auction winners affected by the annulment. The urgency of this research arises from the legal uncertainty that occurs when an auction declared valid under administrative procedure is subsequently cancelled by a court decision, thereby altering the rights and obligations of debtors, creditors, and good faith buyers. Using a normative juridical method through statutory, conceptual, and case approaches, this study draws upon first instance, appellate, and cassation court decisions as primary legal materials. The findings show that the judges cancelled the auction minute deed on the basis of an unlawful act, particularly the creditor’s failure to comply with legal procedures in determining the limit price and the violation of propriety and fairness principles. The legal consequences include the restitution of land rights to the debtor, the nullification of the auction winner’s ownership rights, and the creditor’s obligation to return the auction proceeds. Legal protection for the auction winner is available through the right to seek compensation from the creditor provided that the buyer can demonstrate good faith. This study highlights the need to harmonize justice, utility, and legal certainty in the implementation and judicial review of secured property auctions. Penelitian ini mengkaji pertimbangan yudisial yang mendasari pembatalan Risalah Lelang Nomor 1352 tahun 2010 serta menganalisis konsekuensi hukum yang ditimbulkan dan bentuk perlindungan hukum bagi pemenang lelang yang terdampak oleh pembatalan tersebut. Urgensi penelitian ini muncul dari ketidakpastian hukum yang terjadi ketika suatu lelang yang secara administratif dinyatakan sah kemudian dibatalkan melalui putusan pengadilan sehingga mengubah posisi hak dan kewajiban debitor, kreditor, dan pembeli beritikad baik. Dengan menggunakan metode yuridis normatif melalui pendekatan peraturan perundang-undangan, konseptual, dan kasus, penelitian ini memanfaatkan putusan pengadilan tingkat pertama, banding, dan kasasi sebagai bahan hukum primer. Temuan penelitian menunjukkan bahwa hakim membatalkan risalah lelang berdasarkan adanya perbuatan melawan hukum terutama karena kreditor tidak mematuhi prosedur hukum dalam penetapan harga limit serta melanggar prinsip kepatutan dan keadilan. Konsekuensi hukum dari pembatalan tersebut meliputi pemulihan hak atas tanah kepada debitor, hapusnya hak kepemilikan pemenang lelang, dan kewajiban kreditor untuk mengembalikan hasil lelang. Perlindungan hukum bagi pemenang lelang tersedia melalui hak untuk menuntut ganti rugi kepada kreditor sepanjang pembeli dapat membuktikan iktikad baik. Penelitian ini menegaskan perlunya harmonisasi antara keadilan, kemanfaatan, dan kepastian hukum dalam pelaksanaan dan pengujian yudisial terhadap lelang atas benda jaminan.